Roles of anthropogenic forcings in the observed trend of decreasing late-summer precipitation over the East Asian transitional climate zone - Wei Zhao (Nature Portfolio, 2021)
Abstract Observations indicate that late-summer precipitation over the East Asian transitional climate zone (TCZ) showed a pronounced decreasing trend during 1951–2005. This study examines the relative contributions of anthropogenic [including anthropogenic aerosol (AA) and greenhouse gas (GHG)] and natural forcings to the drying trend of the East Asian TCZ based on simulations from CMIP5. The results indicate that AA forcing plays a dominant role in contributing to the drying trend of the TCZ. AA forcing weakens the East Asian summer monsoon via reducing the land-sea thermal contrast, which induces strong low-level northerly anomalies over eastern China, suppresses water vapor transport from southern oceans and results in drier conditions over the TCZ. In contrast, GHG forcing leads to a wetting trend in the TCZ by inducing southerly wind anomalies, thereby offsetting the effect of the AA forcing. Natural forcing has a weak impact on the drying trend of the TCZ due to the weak response of atmospheric anomalies.